A PC / ABS alloy and its preparation method and application

By extending the melt extrusion time and modifying silica, combined with the generation of zinc sorbate, the problem of recycling ABS plastic and the problem of high-temperature decomposition of PC/ABS alloy is solved, and the mechanical properties and yellowing resistance of the material are improved.

CN118374137BActive Publication Date: 2025-01-24GUANGDONG SEONLON NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410610635.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2025-01-24
Estimated Expiration
2044-05-16

AI Technical Summary

Technical Problem

ABS plastics are difficult to effectively recycle after use, resulting in environmental pollution and health threats. At the same time, the decomposition performance of existing PC/ABS alloys is insufficient at high temperatures, which affects its mechanical properties and yellowing resistance.

Method used

By extending the melt extrusion time and modifying the silica, the compatibility between ABS material and silica is increased, and the zinc sorbate generated in situ during the melt extrusion process is used to improve the compatibility of the ABS material. properties, inhibiting the high-temperature decomposition of polymers.

Benefits of technology

It significantly improves the mechanical properties and yellowing resistance of PC/ABS alloy, extends its service life, and promotes the recycling of ABS plastic.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005047725480000011
    Figure FDA0005047725480000011
  • Figure GDA0005047725490000021
    Figure GDA0005047725490000021
  • Figure GDA0005047725490000041
    Figure GDA0005047725490000041
Patent Text Reader

Abstract

The invention relates to a PC / ABS alloy and a preparation method and application thereof, and belongs to the technical field of PC / ABS alloy. A PC / ABS alloy comprises the following components: PC, modified ABS, modified carbon nanotubes and auxiliary materials; the auxiliary materials are composed of lubricants, antioxidants and anti-UV agents; the modified carbon nanotubes are obtained by modifying carbon nanotubes with silane coupling agents; the preparation method of the modified ABS comprises: after mixing ABS material and modified silicon dioxide, melt extruding, adding sorbic acid and zinc oxide, mixing and melt extruding to obtain modified ABS; the invention increases the compatibility between ABS material and silicon dioxide by modifying silicon dioxide, and plays a reinforcing role through melt extrusion; the zinc sorbate generated in the melt extrusion process improves the compatibility of ABS material in the system, inhibits the high-temperature decomposition of polymers, and strengthens the mechanical properties and yellowing resistance of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PC / ABS alloys and relates to a PC / ABS alloy and a preparation method and application thereof. Background Art

[0002] PC / ABS alloy material, an engineering plastic alloy, has attracted much attention in my country in recent years. It combines the advantages of polycarbonate (PC) and acrylonitrile-butadiene-styrene (ABS) resin, showing excellent heat resistance, weather resistance, dimensional stability and impact resistance, as well as good processing fluidity. Therefore, it is widely used in electronics, electrical appliances, automobiles and other fields.

[0003] In the field of electronics, PC / ABS alloy materials have become an important component of electronic products due to their excellent performance, such as the shells, brackets, buttons and other parts of mobile phones and tablets. Its high heat resistance, dimensional stability and impact resistance improve the service life of the product and user experience.

[0004] In the field of electrical appliances, PC / ABS alloy materials are also very popular. Its excellent heat resistance, weather resistance and impact resistance make it often used to make the shells and parts of household appliances such as televisions, refrigerators, washing machines, etc., which improves the product's ability to resist falling and collision, reduces the failure rate, and ensures user safety.

[0005] In the automotive manufacturing industry, the excellent processing fluidity of PC / ABS alloy materials makes it an ideal choice for automotive interiors, exteriors and key components. These parts are not only beautiful and comfortable, but also have sufficient heat resistance, weather resistance and impact resistance to cope with various extreme conditions.

[0006] ABS plastic waste may age, break and migrate, becoming the main source of microplastics, which not only damages the natural environment but also threatens human health. Therefore, the recycling of ABS plastic is necessary and critical. Usually, people tend to recycle plastics by landfilling, incineration and other treatment methods. Although the cost is low, it will cause irreversible harm to the environment. Summary of the invention

[0007] The purpose of the present invention is to provide a PC / ABS alloy and a preparation method and application thereof. The present invention increases the compatibility between ABS material and silica by appropriately extending the melt extrusion time and modifying silica, and plays a reinforcing role through melt extrusion. In the melt extrusion process, in-situ generated zinc sorbate improves the compatibility of ABS material in the system, inhibits the high-temperature decomposition of polymers, and further enhances the mechanical properties and yellowing resistance of the composite material.

[0008] The purpose of the present invention can be achieved through the following technical solutions:

[0009] A PC / ABS alloy comprises the following components in parts by weight:

[0010]

[0011] As a preferred technical solution of the present invention, the auxiliary material is formed by mixing a lubricant, an antioxidant and an anti-UV agent in a mass ratio of 2.2:1.0-1.3:0.4.

[0012] As a preferred technical solution of the present invention, the lubricant is one or more of TAF, polyethylene wax and calcium stearate.

[0013] As a preferred technical solution of the present invention, the antioxidant is one or both of antioxidant 1010 and antioxidant 168.

[0014] As a preferred technical solution of the present invention, the anti-UV agent is one or both of the ultraviolet absorber UV-9 and the ultraviolet absorber BP-6.

[0015] As a preferred technical solution of the present invention, the modified carbon nanotubes are obtained by modifying the carbon nanotubes with a mass ratio of 1-1.3:12-15 of a silane coupling agent.

[0016] The present invention also discloses a method for preparing the modified ABS, comprising the following steps:

[0017] 1) ABS material and modified silicon dioxide are stirred and mixed, and then melt-extruded to obtain a prefabricated material;

[0018] 2) The preform, sorbic acid and zinc oxide are mixed and melt-extruded to obtain modified ABS.

[0019] As a preferred technical solution of the present invention, in step 1), the melt extrusion conditions are at a temperature of 200-230° C. and melting for 7-10 minutes.

[0020] As a preferred technical solution of the present invention, in step 2), the melt extrusion conditions are at a temperature of 210-230° C. and melting for 9-12 minutes.

[0021] As a preferred technical solution of the present invention, in the preparation of the modified ABS, the mass ratio of the ABS material, modified silica, sorbic acid and zinc oxide is 25-27:8-9:3-3.5:1.5-1.8; the ABS material is selected from ABS waste and purchased from Yangzhou Ningda Precious Metals Co., Ltd.

[0022] The present invention also discloses a method for preparing the modified silicon dioxide, comprising the following steps:

[0023] After mixing silica and anhydrous ethanol, p-aminothiophenol and cinnamaldehyde are added, heated and stirred, and then the solid is filtered, washed and dried to obtain modified silica.

[0024] As a preferred technical solution of the present invention, in the preparation of modified silicon dioxide, the washing is performed 3 times with anhydrous ethanol; the heating and stirring is performed at 50-60°C for 6-8h; and the drying temperature is 80-85°C.

[0025] As a preferred technical solution of the present invention, in the preparation of modified silicon dioxide, the mass ratio of silicon dioxide, anhydrous ethanol, p-aminothiophenol and cinnamaldehyde is 9-12:60-70:3-3.5:4.2-4.8.

[0026] The invention discloses a method for preparing the above-mentioned PC / ABS alloy, which comprises the following steps: weighing PC, modified ABS, modified carbon nanotubes and auxiliary materials according to their mass fractions and adding them into a twin-screw extruder, and performing melt extrusion and granulation at a temperature of 220° C. to obtain the PC / ABS alloy.

[0027] The invention discloses application of a PC / ABS alloy, and the application of the PC / ABS alloy in the fields of electronics, electrical appliances and automobiles.

[0028] As a preferred technical solution of the present invention, the silane coupling agent in the solution of the present invention is silane coupling agent KH560.

[0029] Beneficial effects of the present invention:

[0030] The present invention increases the compatibility between ABS material and silica by appropriately extending the melt extrusion time and modifying silica, and plays a reinforcing role through melt extrusion. In the melt extrusion process, the zinc sorbate generated in situ improves the compatibility of the ABS material in the system, inhibits the high-temperature decomposition of the polymer, and further enhances the mechanical properties and yellowing resistance of the composite material. DETAILED DESCRIPTION

[0031] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0032] Example 1

[0033] A PC / ABS alloy comprises the following components in parts by weight:

[0034]

[0035] The auxiliary material is a mixture of a lubricant, an antioxidant and an anti-UV agent in a mass ratio of 2.2:1.0:0.4;

[0036] The lubricant is prepared by mixing polyethylene wax and calcium stearate in a mass ratio of 3:1;

[0037] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1;

[0038] The anti-UV agent is ultraviolet absorber BP-6.

[0039] The modified carbon nanotubes are obtained by modifying a silane coupling agent and carbon nanotubes in a mass ratio of 1:12.

[0040] The preparation method of the modified ABS comprises the following steps:

[0041] 1) ABS material and modified silicon dioxide are stirred and mixed, and then melt-extruded to obtain a prefabricated material;

[0042] In step 1), the melt extrusion conditions are at a temperature of 200° C. and melting for 7 minutes;

[0043] 2) mixing the preform, sorbic acid and zinc oxide and then melt-extruding to obtain modified ABS;

[0044] In step 2), the melt extrusion conditions are at a temperature of 210° C. and melting for 12 minutes;

[0045] In the preparation of the modified ABS, the mass ratio of the ABS material, modified silicon dioxide, sorbic acid and zinc oxide is 25:8:3:1.5.

[0046] The preparation method of the modified silicon dioxide comprises the following steps:

[0047] After silicon dioxide and anhydrous ethanol are stirred and mixed, p-aminothiophenol and cinnamaldehyde are added, heated and stirred, and then the solid is filtered, washed, and dried to obtain modified silicon dioxide; the washing is performed by washing with anhydrous ethanol for 3 times; the heating and stirring is performed at 50° C. and stirring for 6 hours; the drying temperature is 80° C.; the mass ratio of silicon dioxide, anhydrous ethanol, p-aminothiophenol and cinnamaldehyde is 9:60:3:4.2.

[0048] A preparation method of a PC / ABS alloy comprises the following steps: weighing PC, modified ABS, modified carbon nanotubes and auxiliary materials according to mass fractions and adding them into a twin-screw extruder, and performing melt extrusion and granulation at a temperature of 220° C. to obtain a PC / ABS alloy.

[0049] Example 2

[0050] A PC / ABS alloy comprises the following components in parts by weight:

[0051]

[0052] The auxiliary material is a mixture of a lubricant, an antioxidant and an anti-UV agent in a mass ratio of 2.2:1.1:0.4;

[0053] The lubricant is prepared by mixing polyethylene wax and calcium stearate in a mass ratio of 3:1;

[0054] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1;

[0055] The anti-UV agent is ultraviolet absorber BP-6.

[0056] The modified carbon nanotubes are obtained by modifying a silane coupling agent and carbon nanotubes in a mass ratio of 1.1:13.

[0057] The preparation method of the modified ABS comprises the following steps:

[0058] 1) ABS material and modified silicon dioxide are stirred and mixed, and then melt-extruded to obtain a prefabricated material;

[0059] In step 1), the melt extrusion conditions are at a temperature of 210° C. and melting for 9 minutes;

[0060] 2) mixing the preform, sorbic acid and zinc oxide and then melt-extruding to obtain modified ABS;

[0061] In step 2), the melt extrusion conditions are at a temperature of 220° C. and melting for 10 minutes;

[0062] In the preparation of the modified ABS, the mass ratio of the ABS material, modified silicon dioxide, sorbic acid and zinc oxide is 25.7:8.3:3.2:1.6.

[0063] The preparation method of the modified silicon dioxide comprises the following steps:

[0064] After silica and anhydrous ethanol are stirred and mixed, p-aminothiophenol and cinnamaldehyde are added, heated and stirred, and then the solid is filtered, washed, and dried to obtain modified silica; the washing is performed by washing with anhydrous ethanol for 3 times; the heating and stirring is performed at 53° C. and stirring for 6.7 hours; the drying temperature is 82° C.; the mass ratio of the silica, anhydrous ethanol, p-aminothiophenol and cinnamaldehyde is 10:63:3.2:4.4.

[0065] A preparation method of a PC / ABS alloy comprises the following steps: weighing PC, modified ABS, modified carbon nanotubes and auxiliary materials according to mass fractions and adding them into a twin-screw extruder, and performing melt extrusion and granulation at a temperature of 220° C. to obtain a PC / ABS alloy.

[0066] Example 3

[0067] A PC / ABS alloy comprises the following components in parts by weight:

[0068]

[0069] The auxiliary material is a mixture of a lubricant, an antioxidant and an anti-UV agent in a mass ratio of 2.2:1.2:0.4;

[0070] The lubricant is prepared by mixing polyethylene wax and calcium stearate in a mass ratio of 3:1;

[0071] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1;

[0072] The anti-UV agent is ultraviolet absorber BP-6.

[0073] The modified carbon nanotubes are obtained by modifying a silane coupling agent and carbon nanotubes in a mass ratio of 1.2:14.

[0074] The preparation method of the modified ABS comprises the following steps:

[0075] 1) ABS material and modified silicon dioxide are stirred and mixed, and then melt-extruded to obtain a prefabricated material;

[0076] In step 1), the melt extrusion conditions are at a temperature of 220° C. and melting for 9 minutes;

[0077] 2) mixing the preform, sorbic acid and zinc oxide and then melt-extruding to obtain modified ABS;

[0078] In step 2), the melt extrusion conditions are at a temperature of 225° C. and melting for 10 minutes;

[0079] In the preparation of the modified ABS, the mass ratio of the ABS material, modified silicon dioxide, sorbic acid and zinc oxide is 26.3:8.7:3.3:1.7.

[0080] The preparation method of the modified silicon dioxide comprises the following steps:

[0081] After silica and anhydrous ethanol are stirred and mixed, p-aminothiophenol and cinnamaldehyde are added, heated and stirred, and then the solid is filtered, washed, and dried to obtain modified silica; the washing is performed by washing with anhydrous ethanol for 3 times; the heating and stirring is performed at 57° C. and stirring for 7.3 hours; the drying temperature is 83° C.; the mass ratio of the silica, anhydrous ethanol, p-aminothiophenol and cinnamaldehyde is 11:67:3.3:4.6.

[0082] A preparation method of a PC / ABS alloy comprises the following steps: weighing PC, modified ABS, modified carbon nanotubes and auxiliary materials according to mass fractions and adding them into a twin-screw extruder, and performing melt extrusion and granulation at a temperature of 220° C. to obtain a PC / ABS alloy.

[0083] Example 4

[0084] A PC / ABS alloy comprises the following components in parts by weight:

[0085]

[0086] The auxiliary material is a mixture of a lubricant, an antioxidant and an anti-UV agent in a mass ratio of 2.2:1.3:0.4;

[0087] The lubricant is prepared by mixing polyethylene wax and calcium stearate in a mass ratio of 3:1;

[0088] The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1;

[0089] The anti-UV agent is ultraviolet absorber BP-6.

[0090] The modified carbon nanotubes are obtained by modifying the silane coupling agent and the carbon nanotubes in a mass ratio of 1.3:15.

[0091] The preparation method of the modified ABS comprises the following steps:

[0092] 1) ABS material and modified silicon dioxide are stirred and mixed, and then melt-extruded to obtain a prefabricated material;

[0093] In step 1), the melt extrusion conditions are at a temperature of 230° C. and melting for 10 minutes;

[0094] 2) mixing the preform, sorbic acid and zinc oxide and then melt-extruding to obtain modified ABS;

[0095] In step 2), the melt extrusion conditions are at a temperature of 230° C. and melting for 9 minutes;

[0096] In the preparation of the modified ABS, the mass ratio of the ABS material, modified silicon dioxide, sorbic acid and zinc oxide is 27:9:3.5:1.8.

[0097] The preparation method of the modified silicon dioxide comprises the following steps:

[0098] After silica and anhydrous ethanol are stirred and mixed, p-aminothiophenol and cinnamaldehyde are added, heated and stirred, and then the solid is filtered, washed, and dried to obtain modified silica; the washing is performed by washing with anhydrous ethanol for 3 times; the heating and stirring is performed at 60° C. and stirring for 8 hours; the drying temperature is 85° C.; the mass ratio of the silica, anhydrous ethanol, p-aminothiophenol and cinnamaldehyde is 12:70:3.5:4.8.

[0099] A preparation method of a PC / ABS alloy comprises the following steps: weighing PC, modified ABS, modified carbon nanotubes and auxiliary materials according to mass fractions and adding them into a twin-screw extruder, and performing melt extrusion and granulation at a temperature of 220° C. to obtain a PC / ABS alloy.

[0100] Example 5

[0101] Compared with Example 3, the difference in Example 5 is that the melting time of step 2) is 12 minutes, and the other components, preparation steps and parameters are the same.

[0102] Comparative Example 1

[0103] Compared with Example 3, the difference in Comparative Example 1 is that the melting time in step 1) is 3 minutes, and the other components, preparation steps and parameters are the same.

[0104] Comparative Example 2

[0105] Compared with Example 3, the difference in Comparative Example 2 is that the melting time of step 2) is 15 minutes, and the other components, preparation steps and parameters are the same.

[0106] Comparative Example 3

[0107] Compared with Example 3, Comparative Example 3 is different in that silicon dioxide is used instead of modified silicon dioxide, and the other components, preparation steps and parameters are the same.

[0108] Comparative Example 4

[0109] Compared with Example 3, Comparative Example 4 is different in that aniline is used instead of p-aminothiophenol, and the other components, preparation steps and parameters are the same.

[0110] Comparative Example 5

[0111] Compared with Example 3, Comparative Example 5 is different in that cinnamaldehyde is not used, and the remaining components, preparation steps and parameters are the same.

[0112] Comparative Example 6

[0113] Compared with Example 3, Comparative Example 6 is different in that sorbic acid is not used, and the other components, preparation steps and parameters are the same.

[0114] Comparative Example 7

[0115] Compared with Example 3, Comparative Example 7 is different in that zinc oxide is not used, and the other components, preparation steps and parameters are the same.

[0116] The PC / ABS alloys prepared in Examples 1-5 and Comparative Examples 1-7 were tested as follows, and the test results are shown in Table 1.

[0117] Tensile strength test: 25℃, tested in accordance with ASTM D638;

[0118] Yellowing resistance test: put it in an aging box at 120℃ for 24h and observe the surface color;

[0119] Table 1

[0120] Tensile strength(MPa) Yellowing resistance Example 1 78 No change Example 2 79 No change Example 3 82 No change Example 4 80 No change Example 5 79 No change Comparative Example 1 66 Small part turns yellow Comparative Example 2 70 Small part turns yellow Comparative Example 3 52 Partially yellowed Comparative Example 4 58 Partially yellowed Comparative Example 5 59 Partially yellowed Comparative Example 6 63 Small part turns yellow Comparative Example 7 58 Partially yellowed

[0121] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-7, the tensile strength and yellowing resistance of the PC / ABS alloy prepared in Examples 1-5 of the present invention are better than those of Comparative Examples 1-7; this is because the present invention breaks the carbon-carbon double bonds in the PB phase of the ABS material by appropriately extending the melt extrusion time, forming more oxygen-containing functional groups, and the oxygen-containing functional groups can attract modified silica containing mercapto groups, non-polar benzene rings and unsaturated carbon-carbon double bonds, increase the compatibility of the two, and play a reinforcing role through melt extrusion. The introduction of oxygen-containing functional groups and mercapto groups can have electrostatic and coordination bond effects on zinc ions, further enhancing the mechanical properties and stability of the composite material. During the melt extrusion process, the in-situ generated zinc sorbate generates free radicals that can undergo a grafting reaction with the PB phase in the ABS material, and utilizes the ionic interaction between zinc ions and unsaturated carboxylates to improve the compatibility of the ABS material in the system. The introduction of zinc can inhibit the high-temperature decomposition of the polymer, further increasing the mechanical properties and yellowing resistance of the composite material.

[0122] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A PC / ABS alloy, characterized in that: The components include the following by weight: The preparation method of the modified ABS comprises the following steps: 1) ABS material and modified silica are stirred and mixed, and then melt-extruded to obtain a prefabricated material; the melt-extrusion conditions are at a temperature of 200-230° C. and melting for 7-10 minutes; 2) Mixing the preform, sorbic acid and zinc oxide and performing melt extrusion to obtain modified ABS; the melt extrusion conditions are at a temperature of 210-230° C. and a melting time of 9-12 minutes; In the preparation of the modified ABS, the mass ratio of the ABS material, modified silicon dioxide, sorbic acid and zinc oxide is 25-27:8-9:3-3.5:1.5-1.8; The preparation method of the modified silicon dioxide comprises the following steps: After silicon dioxide and anhydrous ethanol are stirred and mixed, p-aminothiophenol and cinnamaldehyde are added, heated and stirred, and then the solid is filtered, washed, and dried to obtain modified silicon dioxide; the heating and stirring is at 50-60° C. and stirred for 6-8 hours; the mass ratio of silicon dioxide, anhydrous ethanol, p-aminothiophenol and cinnamaldehyde is 9-12:60-70:3-3.5:4.2-4.

8.

2. A PC / ABS alloy according to claim 1, characterized in that: The auxiliary material is prepared by mixing a lubricant, an antioxidant and an anti-UV agent in a mass ratio of 2.2:1.0-1.3:0.

4.

3. A PC / ABS alloy according to claim 2, characterized in that: The lubricant is one or more of TAF, polyethylene wax and calcium stearate; the antioxidant is one or both of antioxidant 1010 and antioxidant 168; the anti-UV agent is one or both of ultraviolet absorber UV-9 and ultraviolet absorber BP-6.

4. The PC / ABS alloy according to claim 1, characterized in that: The modified carbon nanotubes are obtained by modifying the silane coupling agent and the carbon nanotubes in a mass ratio of 1-1.3:12-15.

5. The PC / ABS alloy according to claim 1, characterized in that: In the preparation of modified silicon dioxide, the washing is performed by washing with anhydrous ethanol for 3 times; and the drying temperature is 80-85°C.

6. A method for preparing a PC / ABS alloy as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: weighing PC, modified ABS, modified carbon nanotubes and auxiliary materials according to mass fractions and adding them into a twin-screw extruder, and performing melt extrusion and granulation at a temperature of 220° C. to obtain a PC / ABS alloy.

7. Use of the PC / ABS alloy according to any one of claims 1 to 5, characterized in that: The PC / ABS alloy is used in the fields of electronics, electrical appliances and automobiles.

Citation Information

Patent Citations

  • PC-ABS electromagnetic shielding composite material and preparation method and application thereof

    CN115746531A